The Cultural Dimensions of Clothing Store Facades in Abha: A Semiotic Approach - Ahmed Al-Hassami, ahmed.cef (El Omda in Linguistics and Discourse Analysis, 2018)
Abstract: The study attempts to examine the language of advertising speech at the front billboards of the clothes stores in Abha from a semiotic aspect in order to highlight the ciphered cultural dimensions of language of this speech. Culture is a system of signs and patterned symbols, which operate in the minds of the society, and direct their behaviors and attitudes into the various walks of life. Thus, the advertising speech at the billboards of stores does not only limit itself within the boundary of advertising and marketing products in a profitable manner; it aims at transferring the producer’s culture to the consumers’ and vice versa. Furthermore, the study aims to explore these cultural aspects with their principles, values and attitudes through tracing its firm evidence in the advertising speech. The research gains its privacy via associating it with Abha City. Therefore, it aims at deepening the identity of belonging to this beautiful and spectacular place, for it is the capital of tourism, and it carries a cultural dimension that enhances the notion of belonging to such a place.